Effect of Calcium Carbonate Content on the Mechanical and Thermal Properties of Chitosan-Coated Poly(urethane) Foams - Elvi Kustiyah; Achmad Nandang Roziafanto; Majid Amrullah; Dedi Priadi; Mochamad Chalid (Indonesian Journal of Chemistry, 2022)
In this work, the effect of chitosan and CaCO3 coating on polyurethane (PU) foam on the mechanical and thermal properties was studied. PU-foams were soaked in a mixture of chitosan- calcium carbonate solution at different concentrations, i.e., 0.1–0.4%. The molecular behaviors due to the incorporation of chitosan/CaCO3 into the PU-foam matrix were investigated by Fourier-Transform Infrared (FTIR) spectroscopy. Field Emission Scanning Electron Microscope (FE-SEM) was utilized to study the effect of chitosan/CaCO3 coat on the pore structure of PU-foam. FTIR spectra show changes in the peak of 1446 and 1413 cm–1, which serve as evidence of molecular interaction between PU and chitosan/CaCO3. FE-SEM images show that the addition of chitosan/calcium carbonate cells was starting to close together, probably due to the increased dispersion of calcium carbonate on the entire surface of PU-foams/chitosan, which indicates that reducing the size of the cell will increase mechanical properties. From this study, it was found that PU-foam soaked in 0.4% CaCO3 had the highest tensile strength. Coating PU-foam with 0.4% CaCO3 also improved its thermal stability, indicated by an increase in its residual mass compared to neat PU-foam.